2015
DOI: 10.4155/fmc.15.85
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Drugs in Refractory Colorectal Cancer

Abstract: Colorectal cancer is the third leading cause of cancer-related deaths in the western world. Despite therapeutic advances, the prognosis of metastatic colorectal cancer patients remains poor due to intrinsic or acquired tumor drug resistance. The main mechanisms of tumor drug resistance are represented by genetic and epigenetic alterations. This leads to tumor refractoriness during treatment or disease progression following response to first-line therapy. Strategies to combat chemorefractory tumors involve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Exosomal miR-19b participates in oxaliplatin sensitivity. Based on the results of Fang et al [22], 10 miRNAs were selected, and QPCR was used to analyze the differences in levels between untreated sw480 cells and sw480 cells treated with 20 μM oxaliplatin for an extended period [21]. miR-19b was the miRNA which attracted our attention ( Figure 3A), because our previous studies proved that miR-19b functions as an oncogene in lung cancer and breast cancer [23], and miR-19a also functions similarly in colorectal cancer [24].…”
Section: Oxaliplatin Inhibits Proliferation Of Sw480 Cellsmentioning
confidence: 99%
“…Exosomal miR-19b participates in oxaliplatin sensitivity. Based on the results of Fang et al [22], 10 miRNAs were selected, and QPCR was used to analyze the differences in levels between untreated sw480 cells and sw480 cells treated with 20 μM oxaliplatin for an extended period [21]. miR-19b was the miRNA which attracted our attention ( Figure 3A), because our previous studies proved that miR-19b functions as an oncogene in lung cancer and breast cancer [23], and miR-19a also functions similarly in colorectal cancer [24].…”
Section: Oxaliplatin Inhibits Proliferation Of Sw480 Cellsmentioning
confidence: 99%
“…Due to the higher incidence and mortality of CRC, investigators have paid more attention on its pathogenic mechanism, as well as the identification of novel anti-CRC drugs 16 , 17 . Previous studies revealed that many natural products can inhibit the development, the identification of more efficient anti-tumor drugs, and also the understanding of underlying molecular mechanisms is also necessary because of the complex pathogenic mechanism in CRC.…”
Section: Discussionmentioning
confidence: 99%